2007
DOI: 10.1039/b615455g
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and structures of the initial stages of nucleation of (SiO2)Nspecies: possible routes to highly symmetrical tetrahedral clusters

Abstract: A detailed survey of the low energy isomer spectrum of (SiO(2))(N), N= 6-10, 13, 16 has been performed using interatomic potential based global optimisations refined via high-level density functional calculations. Within these spectra, including many isomers reported for the first time, structurally and energetically viable pathways for the initial stages of silica cluster growth through SiO(2) nucleation are identified. The role of the exceptionally stable (SiO(2))(8) ground state "magic" cluster is highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Theoretical studies of smallsize silica clusters have revealed diverse metastable building blocks with chain [5,6], ring [7][8][9], cage [10], and tubular [11,12] configurations formed by assembling two-, three-and four-membered rings (2MRs, 3MRs, and 4MRs). Using a global optimization algorithm, Bromley et al, predicted the ground state candidates for the (SiO 2 ) N cluster with N = 6-27 [13][14][15], which are more stable than the other available clusters of similar size. The structures of these clusters differ significantly from the network of silicon-centered corner-sharing SiO 4 tetrahedral of bulk silica where six-membered rings (6MRs) were found to be the most frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies of smallsize silica clusters have revealed diverse metastable building blocks with chain [5,6], ring [7][8][9], cage [10], and tubular [11,12] configurations formed by assembling two-, three-and four-membered rings (2MRs, 3MRs, and 4MRs). Using a global optimization algorithm, Bromley et al, predicted the ground state candidates for the (SiO 2 ) N cluster with N = 6-27 [13][14][15], which are more stable than the other available clusters of similar size. The structures of these clusters differ significantly from the network of silicon-centered corner-sharing SiO 4 tetrahedral of bulk silica where six-membered rings (6MRs) were found to be the most frequent.…”
Section: Introductionmentioning
confidence: 99%
“…One would have in mind that the free energy of formation of small undercritical clusters depends on the cluster structure, which can differ even for the same cluster size (Bromley & Illas, 2007;Connerade, 2002;Ong & Tok, 2007). It is known that the so-called magic numbers of clusters correspond to the local minimum of the cluster energy in the dependence of their size.…”
Section: Modelmentioning
confidence: 99%
“…Various methods (Bartell & Huang, 1998;Bromley & Illas, 2007;Debenedetti & Reiss, 1998;Kashchiev, 2003Kashchiev, , 2004Meng, Rong, & Hsu, 2002;Nellas & Chen, 2008) have been used to determine the nucleation barrier. Some approaches are based on thermodynamically consistent formalism (Debenedetti & Reiss, 1998;Kashchiev, 2003Kashchiev, , 2004, other on molecular dynamics calculations (Bartell & Huang, 1998), on the concepts of surface stress associated with phase equilibria (Meng et al, 2002), atomistic simulations (Nellas & Chen, 2008), or density functional calculations (Bromley & Illas, 2007). In standard nucleation theory the capillarity approximation is usually used and the work of formation of nuclei is thus given by…”
Section: Modelmentioning
confidence: 99%
“…A number of recent studies have employed this potential together with the basin hopping (BH) global optimization approach [45] and subsequent energetic/structural refinement using DFT in order to obtain ground state candidates for (SiO 2 ) N N ¼ 6-27 [46][47][48][49]. The somewhat arbitrary partial charges of 2.4e for the silicon atoms and À 1.2e for the oxygen atoms (as successfully used in other similar potentials) are additionally employed to provide long-range electrostatic interactions between all atoms.…”
Section: Theoretical Studies Of Low-energy (Sio 2 ) N Clustersmentioning
confidence: 99%
“…It is noted that this increase in structural complexity is mirrored in the increased difficultly in mapping the low-energy (SiO 2 ) 6 energy landscape, whereby two of the low-energy isomers in Figure 2 (e.g., 6e, 6f) have been obtained only via use of global optimization [46,49]. This cluster size marks a crossover point in the evolution of silica cluster structure with increasing size where we pass from a preference for one-dimensional growth to more complex growth trends for (SiO 2 ) N N > 6.…”
Section: Low-energy (Sio 2 ) 6 Cluster Isomersmentioning
confidence: 99%